Electromyographic Activity of Masticatory Muscles in Asymptomatic Young Adults - Wieczorek, Aneta; Pihut, Malgorzata; Loster, Jolanta E. (Journal of Dentistry Indonesia, 2022)
Introduction: The masseter and the anterior part of the temporalis are the muscles mainly responsible for the clenching function. Clenching patterns and the activity of these muscles are not expected to differ between male and females, nor between different occlusal classes. Objective: The aim of this study was to determine whether the activity index of the masseter and temporalis muscles is related to occlusal class and gender. Methods: This study involved 145 eighteen-year-old Caucasian volunteers who underwent surface electromyography. The sEMG was analyzed at the moment of 100% occlusal contact. Occlusal classes were determined used plaster casts. Results: The Class I group contained 34 males and 63 females, while Class II had 11 males and 25 females. Comparison of the AcI data showed an insignificant relation between the genders in the activity indices of Classes I and II. Significant relation between male gender and predominance of the masseter muscles, as well as between female gender and an almost equal balance between the muscles, though with a tendency towards a predominance of the temporalis anterior. Conclusion: The activity of masseter muscles during clenching the teeth is bigger in the male than in the female group. Activity index is related to gender.